Oral health of building construction workers: an epidemiological approach Saúde bucal de trabalhadores da construção civil: abordagem epidemiológica - Nilce Emy Tomita; Luiz Eduardo Montenegro Chinellato; José Roberto Pereira Lauris; Cláudia Minami Kussano; Haroldo José Mendes; Maria Teresa Valente Cardoso (University of São Paulo, 2005)
This cross-sectional study aimed at evaluating the oral health conditions of building construction workers from a city in the mid-west region of São Paulo, Brazil. This study involved 219 male subjects, aged 17 to 72. The definition of a random sample utilized the functional number of each worker as a criterion to the raffle, which took into account all 450 subjects registered in the Working Accidents Prevention Program. The examination of oral health conditions by DMFT index and need of treatment were carried out according to WHO criteria (1997). This paper reports the prevalence of caries according to age, occupation, and educational level. Among the 219 workers examined, the mean DMFT was 16.9. Amongst the younger workers (<25 years-old), 21.3 teeth showed no need of treatment, while the older ones showed increasing treatment needs (p<0.001). The DMFT values were 15.6 for the administrative duties and 21.7 for foremen and bricklayers, although the differences were not statistically significant. The DMFT index showed an increase with age for all groups (p<0.001). The self-reported need of treatment was associated with a smaller DMFT for people that reported a positive response when compared with subjects that did not report these needs (p<0.05). These differences were statistically significant, as tested by ANOVA and Student t test. Among the building construction workers, in this study, important oral lesions were not observed, despite the daily exposition to some risk factors for oral cancer. Este estudo transversal foi delineado para avaliar as condições de saúde bucal de trabalhadores da construção civil em município da região centro-oeste do Estado de São Paulo. Foram examinados 219 indivíduos do sexo masculino, com idades entre 17 e 72 anos. O levantamento das condições bucais foi realizado em processo de amostragem aleatória simples, a partir do total de 450 inscritos na MEGA-SIPAT 2000 (Semana Interna de Prevenção de Acidentes do Trabalho). Foi utilizado o índice CPOD (cárie dentária) e necessidade de tratamento odontológico, segundo metodologia proposta pela Organização Mundial da Saúde (1997). Neste estudo, são descritas a prevalência de cárie segundo a idade, ocupação e escolaridade. Entre os 219 trabalhadores examinados, o valor CPOD apurado foi 16,9. Os trabalhadores mais jovens (<25 anos de idade) apresentaram média de 21,3 dentes sem necessidade de tratamento, enquanto os mais velhos mostraram necessidades progressivas de tratamento restaurador e reabilitador (p<0,001). Verificou-se índice CPOD de 15,6 para os trabalhadores de áreas administrativas e 21,7 para os mestres-de-obras, sem significância estatística. Houve aumento do índice CPOD segundo a idade, para todos os grupos de trabalhadores (p<0,001). A necessidade de tratamento auto-referida mostrou-se associada a valores CPOD mais baixos para os indivíduos que relataram resposta positiva, quando comparado àqueles que não apresentavam percepção de tais necessidades (p<0,05). Estas diferenças foram significantes, à análise de variância e teste t de Student. Para os trabalhadores da construção civil, neste estudo, não foram observadas lesões orais importantes, presentes em apenas 2,7% dos indivíduos, apesar da exposição diária a alguns fatores de risco para câncer de boca.